The Pragmatics of Publishers’ Intentions on the Linguist List Journal Publication Calls (2014)
The Linguist List Web site is a forum where professionals exchange academic information, especially those related to conferences, calls for papers for journals and books, mailing lists and job opportunities. While all these are constructed in scholarly language, the ones with the most distinguished linguistic form, often with pragmatic meaning, whose proper interpretation has implications for linguists‟ careers, are calls for journal articles posted by publishers. Scholarly information on the Linguist List site has covered site description and scope of operation, but little scholarly work has been attempted on the pragmatic features of the posts, especially journal calls, in spite of its impact on academics‟ professional life. This study, therefore, examined the locutions and illocutionary acts performed in the journal call discourses on the site with a view to establishing the link between the linguistic forms and pragmatic functions in the discourse and their implications for linguists‟ publication prospects. The study adopted a descriptive design and Searle‟s speech act theory, utilising only the locutionary and illocutionary aspects of the theory because of their potency to show a link between linguistic choices and language users‟ intentions. Stratified and purposive sampling techniques were used to select 115 (25% of the 460 posts on the site) journal call posts which comprised pure linguistics (38), applied linguistics (56) and interdisciplinary linguistics (21) on 17December, 2011 from http://linguistlist.org/browse-journals.cfm. Data were subjected to pragmatic analysis. Two levels of locutions were found: lexico-semantic and syntactic levels. The lexicosemantic level covered vocabulary which pointed to the scope of the journals (SJ), academic practice (AP), publication process (PP), editorial composition (EC) and peerreview (PR). Paradigmatic features (synonyms related to PP, SJ, and subscriber‟s status (SS); antonyms revealing research methodology (RM), SJ, PP, and SS were observed. Syntagmatic elements included collocates which showed JT, SJ, RM, PP, paper solicitation (PS), journals utility (JU), and journals‟ access types (AT). At the syntactic level, sentence types revealed simple, compound, complex and anomalous sentences. Except synonyms related to JS and SS which were peculiar to interdisciplinary journals, all other features were common to all the posts. Seven illocutionary acts manifested in the journal posts: Explaining, Preferring, Describing, Mentioning, Proposing, Restricting and Claiming. In the SJ, JU, SS, and PP, the publishers Explained, Preferred, Described, Mentioned and Proposed. They Claimed in PS, AT, JU and PP; and Restricted in SJ, RM, SS and PP. One level of pragmatic communication occurred in the discourse: Indirect communication achieved through non-IFID-(Illocutionary force indicating device) driven acts. While Explaining, Describing and Mentioning acts pragmatically guided scholar-audience‟s choice of journals and professional output; Proposing, Preferring, Restricting and Claiming intimated them with the expected scholastic standards of the journals, charged them with self-evaluation and check listing prior to submission, and hinted at the possibility of failure. Locutions and pragmatic functions of publishers‟ discourse on the Linguist List Web site symbiotically revealed the linguistic forms and pragmatic communication of publishers. These unveil the publishers‟ intentions and the implications of their effectiveness or otherwise for academic publications in the posted journals